2007
DOI: 10.1523/jneurosci.2939-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Top–Down Attentional Deficits in Macaques with Lesions of Lateral Prefrontal Cortex

Abstract: Brain imaging, electrical stimulation, and neurophysiological studies have all implicated the prefrontal cortex (PFC) in the top-down control of attention. Specifically, feedback from PFC has been proposed to bias activity in visual cortex in favor of attended stimuli over irrelevant distracters. To identify which attentional functions are critically dependent on PFC, we removed PFC unilaterally in combination with transection of the corpus callosum and anterior commissure in two macaques. In such a preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
127
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(145 citation statements)
references
References 78 publications
17
127
1
Order By: Relevance
“…These results suggest that the PFC plays a broader role in executive functioning including both top-down attentional control and VWM maintenance, whereas the BG are more directly related to global VWM maintenance processes, extending the role of the BG outside the motor domain. Several studies have reported VWM deficits after lateral PFC damage (1)(2)(3). In contrast, BG lesions lead to a VWM behavioral impairment associated with maintenance deficits despite intact attention mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that the PFC plays a broader role in executive functioning including both top-down attentional control and VWM maintenance, whereas the BG are more directly related to global VWM maintenance processes, extending the role of the BG outside the motor domain. Several studies have reported VWM deficits after lateral PFC damage (1)(2)(3). In contrast, BG lesions lead to a VWM behavioral impairment associated with maintenance deficits despite intact attention mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In essence, we construct and hold a model of the visual world and compare that model against subsequent inputs from the external world. VWM relies upon an intact and functioning prefrontal cortex (PFC), and damage to this region, such as from stroke, causes VWM impairments (1)(2)(3). However, cognitive processes do not localize to specific brain regions per se and a behavior as complex as VWM recruits a distributed network of cortical and subcortical structures (4)(5)(6)(7)(8), including the basal ganglia (BG) (9,10) and visual extrastriate regions (11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whether and how attention modulates ongoing brain activity when it is deployed in advance of sensory stimulation has also attracted increased research interest (Kastner et al, 1999;Driver and Frith, 2000;Pasternak and Greenlee, 2005;Procyk and Goldman-Rakic, 2006;Fuster, 2008). This internally generated expectancy state improves behavioral performance by shortening reaction time and reducing the number of errors and is thought to be implemented by top-down control mechanisms (Knight et al, 1999;Hopfinger et al, 2000;Miller, 2000;Engel et al, 2001;LaBerge, 2005;Buschman and Miller, 2007;Rossi et al, 2007;Fuster, 2008;Gregoriou et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Neurocomputational models of basal ganglia function has shown us that this model can select the action or make the frontal cortical express a reward or to a correct feedback, reducing the occurrence of errors or negative feedback [7]. The frontal lobe is the most advanced part offound that a visual working memory can be impaired if prefrontal cortex is damaged [10,11]. The prefrontal cortex plays an important role in encode, update and maintain the working memory task context [12].…”
Section: Introductionmentioning
confidence: 99%